Pengaruh Audit Tenure, Debt Default tehadap Penerimaan Opini Audit Going Concern pada Perusahaan Manufaktur Sektor Aneka Industri yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2021 - Kintan Diandra Sabilla; Eka Fauzihardani (Universitas Negeri Padang, 2024)
This study aims to find out how tenure and debt default audits affect going-concern audit opinions. This research focuses on manufacturing companies in the various industrial sectors listed on the Indonesia Stock Exchange for the 2017-2021 period. The purposive sampling method was used to select the sample in this study, namely 49 companies. Based on the process of data collection, data processing and data testing, the overall summary of the results of the research is presented from the interpretation of the data, namely the tenure audit variable positively influences acceptance of going-concern opinions but is not significant so that it is stated that tenure audits do not influence acceptance of going-concern opinions. concern. Meanwhile, the debt default variable has a positive and significant effect so that it can be stated that debt default has an influence on receiving a going concern opinion.